Financial Inclusion in the Agricultural Sector in Nigeria: An Index of Penetration - Kalu, Ugbor I.; Omeje, Ambrose Nnaemeka; Mba, Augustine Jideofor (International Journal of Economics and Financial Issues, 2018)
This study investigated financial inclusion in the agricultural sector in Nigeria. The study utilized survey data generated from 600 recovered questionnaires which were administered to farmers in both rural and urban locations in Nigeria. The study developed adequacy gap index and timeliness gap index to measure the penetration gap index theory of financial inclusion through the application of the pecking order theory. The adequacy and timeliness gap indices revealed that the different formal lending agencies were unable to meet the credit needs of these small scale farmers hence, credit was inadequately and untimely provided to small scale farmers because they depend on rain-fed agriculture. The penetration gap index revealed that the penetration of financial inclusion in agricultural sector is still shallow in Nigeria. It was recommended among others that government should intensify the efforts to meet the credit needs of farmers (adequacy and timeliness) to ensure the penetration of financial inclusion. Keywords: Financial Inclusion, Agricultural Sector, Adequacy Gap Index, Timeliness Gap Index, Penetration Index JEL Classifications: A1, B1, B41, D2, D3, G, H3